Does Hard Work Pay Off? The Influence of Perceived Effort on Romantic Attraction - Jennifer R. Dwiggins; Gary W. Lewandowski (Interpersona: An International Journal on Personal Relationships, 2015)
This study examines how a person’s willingness to exert effort affects how others perceive their romantic desirability. The study also examines whether the participants’ implicit theory of personality (incremental or entity) influences ratings of the target’s romantic desirability based on the target’s level of effort. Seventy-eight (17 males, 61 females) single college students participated in the study. Participants read one of four descriptions of a target. The descriptions manipulated both the target’s ability (hard work or natural ability) and success (successful or unsuccessful). Participants also completed a measure to assess their implicit theory of personality. Participants then rated the target’s desirability. There was a significant difference in desirability ratings of the target for the main effect of ability. There were no other significant differences found between the variables. The findings suggest that when a person expends effort, they are more romantically desirable regardless of how successful they are. Findings also suggest that a person’s implicit theory of personality does not interact with the target’s effort to affect romantic desirability.